(untitled) (Journal of Comparative & International Higher Education, 2022)
In this article, we examined the impact of COVID-19 on international students’ experience and highlighted the importance of supporting this student group. We drew on findings from a mixed methods study in North Queensland, Australia. First, we discussed mental well-being and analysed how the COVID-19 pandemic has impacted individuals’ mental health and well-being. We linked our analysis to international students’ vulnerability and well-being, looking specifically at the impact of financial and emotional distress. The findings of our study provided knowledge regarding the challenges international students face in North Queensland. In order to better meet the needs of international students, we argue that higher education institutions must provide tailored programs and services, including nurturing, supportive, responsive, and needs-orientated environments, to address the challenges international students face, and the mental health needs posed by the pandemic and beyond.